Black female managers perceptions’ of integration into informal social networks at work - Motlhamme, Kelebogile Faith (My University, 2018)
The objective of this research was to identify Black female Managers perceptions’ of integration into informal social networks at work. Informal social networks have been identified as one of the ways of improving career success. Given the low representation of Black female managers in South African organisations, identifying their perceptions of informal social networks could assist in increasing the number of Black women in managerial roles. Two specific aims were established for this research, firstly to distinguish the participants’ perceptions of informal social networks at work, and to identify the strategies that they use to manage their integration into these informal social networks. The study was carried out using a qualitative research design, where data was collected through face-to-face interviews using a semi-structured interview guide. The sample consisted of 9 Black female managers from various organisations in Johannesburg, ages between 24-55 years. The data was analysed using thematic analysis. The results showed that majority of the participants do not see themselves as being involved in informal social networks in the workplace although most participated in informal relationships with certain colleagues at work. Implications of the study include reviewing the concept of informal social networks, due to the complexity involved in distinguishing the relational properties of informal social networks at work and understanding the impact sense of agency has on the integration strategies used by Black female managers.
A research project submitted in partial fulfilment of the requirements for the degree of MA by coursework and Research Report in the field of Industrial Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg February 2018
Keywords: Sex role in the work environment--South Africa; Women executives--South Africa; Executives, Black--South Africa; Women, Black--South Africa--Social conditions; Women, Black--South Africa--Economic conditions